2021
DOI: 10.1007/s40256-021-00480-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolocumab’s Long-Term Mortality Risk Unclear Due to Shortened Follow-Up of FOURIER

Abstract: The FOURIER (Further Cardiovascular Outcomes Research with PCSK9 inhibition in Subjects with Elevated Risk) trial was conducted to study cardiovascular outcomes of treatment with evolocumab. The trial was terminated after a median follow-up of 2.2 years instead of the planned 3.6 years. We question this decision. According to the investigators, the event rate was 50% higher than expected. However, the accrued number of key secondary events (1829) was only 12% higher than the targeted number (1630). Also, aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although very low levels of non-HDL cholesterol are related to a reduction in cardiovascular disease events, 24,25 some observations point toward higher all-cause mortality among participants with very low levels, at least in longer-term follow-up. 26 In contrast to what was previously reported, 3 body-mass index and current smoking (at least in some parts of the world) were associated with comparatively modest populationattributable fractions of cardiovascular disease events in the populations participating in the Global Cardiovascular Risk Consortium. These associations may be related to underlying differences in population characteristics, risk-factor definition and prevalence, or methods used to estimate population-attributable fractions.…”
Section: Discussionmentioning
confidence: 59%
“…Although very low levels of non-HDL cholesterol are related to a reduction in cardiovascular disease events, 24,25 some observations point toward higher all-cause mortality among participants with very low levels, at least in longer-term follow-up. 26 In contrast to what was previously reported, 3 body-mass index and current smoking (at least in some parts of the world) were associated with comparatively modest populationattributable fractions of cardiovascular disease events in the populations participating in the Global Cardiovascular Risk Consortium. These associations may be related to underlying differences in population characteristics, risk-factor definition and prevalence, or methods used to estimate population-attributable fractions.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, according to data derived from ClinicalTrial.gov, in the FOURIER trial on participants with 3 years of follow-up, the cumulative all-cause mortality rate was 4.75% for the evolocumab group and 4.28% for the placebo group [Figure 1 ]. [ 24 ] Data derived from the ClinicalTrial.gov for a total of 33 lipid-lowering and four outcome trials showed that PCSK9i even did not reduce myocardial infarction nor stroke/transient ischemic attack compared with placebos. [ 25 ]…”
Section: Aggressive Lipid-lowering and Cardiovascular And All-cause M...mentioning
confidence: 99%
“…Notably, according to data derived from ClinicalTrial.gov, in the FOURIER trial on participants with 3 years of follow-up, the cumulative all-cause mortality rate was 4.75% for the evolocumab group and 4.28% for the placebo group [Figure 1]. [24] Data derived from the ClinicalTrial.gov for a total of 33 lipid-lowering and four outcome trials showed that PCSK9i even did not reduce myocardial infarction nor stroke/transient ischemic attack compared with placebos. [25] Apart from the ODYSSEY OUTCOMES trial on patients who had an ACS 1 to 12 months earlier, there is limited real-world evidence of the impact of PCSK9i therapy on cardiovascular outcomes in patients with a very high risk of ASCVD (as defined by at least two severe ASCVD events or one severe event combined with at least two high-risk factors).…”
Section: Aggressive Lipid-lowering and Cardiovascular And All-cause M...mentioning
confidence: 99%
See 2 more Smart Citations